Wnts Promote Synaptic Assembly Through T-Cell Specific Transcription Factors in Caenorhabditis elegans - Shi, Yanjun; Li, Qian; Shao, Zhiyong (Frontiers in Molecular Neuroscience, 2018)
Synapses are specialized neuronal connections essential for neuronal function. Defects in synaptic assembly or maintenance usually lead to various neurological disorders. Synaptic assembly is regulated by secreted molecules such as Wnts. Wnts are a large family of conserved glycosylated signaling molecules involved in many aspects of neural development and maintenance. However, the molecular mechanisms by which Wnts regulate synaptic assembly remain elusive due to the large number of ligands/ receptors, the diversity of signaling cascades, and the complexity of the nervous system. In this study, through genetic manipulation, we uncover that C. elegans Wnt-2 (CWN-2) is required for synaptic development. The CWN-2 signal is required during both embryonic and postembryonic development, in the nervous system and intestine, for promoting synaptic assembly. Furthermore, we provide genetic evidence for CWN-2 promoting synaptogenesis through the Frizzled receptor CFZ-2, the Dishevelled DSH-2, the β-catenin SYS-1 and the only T-cell specific transcription factor POP-1/TCF. Importantly, it is the first time to report that the requirement of a TCF for presynaptic assembly. These findings expand our understanding of the synaptogenic mechanisms and may provide therapeutic insights into Wnt-related neurological disorders.